TRAF4 Inhibits the Apoptosis and Promotes the Proliferation of Breast Cancer Cells by Inhibiting the Ubiquitination of Spindle Assembly-Associated Protein Eg5 - Hao, Miaomiao; Zhang, Jie; Sun, Mingfang; Diao, Kexin; Wang, Jian; Li, Shiping; Cao, Qixue; Dai, Shundong; Mi, Xiaoyi (Frontiers in Oncology, 2022)
Tumor necrosis factor receptor associated factor 4 (TRAF4) is a RING domain E3 ubiquitin ligase that mediates the ubiquitination of various proteins and plays an important role in driving tumor progression. By studying the relationship between TRAF4 and Eg5, a member of the kinesin family that plays a critical role in spindle assembly, we demonstrated that TRAF4 regulated Eg5 ubiquitination and contributed to Eg5-mediated breast cancer proliferation and inhibited breast cancer apoptosis. TRAF4 and Eg5 were both highly expressed in breast cancer and their protein level was positively correlated. Relying on its Zinc fingers domain, TRAF4 interacted with Eg5 in the cytoplasm of breast cancer cells. TRAF4 was a mitosis-related protein, and by up-regulating the protein level of Eg5 TRAF4 participated in spindle assembly. Loss of TRAF4 resulted in monopolar spindles formation, but loss of function could be rescued by Eg5. Relying on its RING domain, TRAF4 up-regulated Eg5 protein levels by inhibition of Eg5 ubiquitination, thus stabilizing Eg5 protein level during mitosis. Furthermore, we found that Smurf2, a TRAF4-targeted ubiquitination substrate, mediated the regulation of Eg5 ubiquitination by TRAF4. TRAF4 inhibited the interaction between Smurf2 and Eg5, and down-regulated the protein level of Smurf2 by promoting its ubiquitination, thereby inhibited the Smurf2-catalyzed ubiquitination of Eg5 and up-regulated Eg5 protein levels. We also demonstrate that TRAF4 plays an important role in promoting cell proliferation and in inhibiting cell apoptosis induced by Eg5. In summary, our study suggests a new direction for investigating the role of TRAF4 in driving breast cancer progression.